Analysis of Students’ Perceptions of Online Learning Media During the Covid-19 Pandemic (Study of E-learning Media: Zoom, Google Meet, Google Classroom, and LMS) - Ikhsan Fuady; Moch. Armien Syifaa Sutarjo; Erna Ernawati (RIRAI Publisher, 2021)
Learning in the pandemic period requires students to be able to use a variety of online learning media. Zoom, Google meet, Google classroom, and LMS platforms are the most frequently used media. Students' behavior to use learning media is influenced by perceptions of the learning media. This study aimed to describe the ease and usefulness perceptions that students feel about the various available learning media. This research is designed as quantitative research with a survey approach. Data analysis was carried out using descriptive statistics. The results show that students' perceived ease of learning media, namely Zoom, Google meet, Google classroom, and LMS, is perceived as relatively easy. Zoom is an application/platform that is considered the easiest of the other media, while LMS is considered more complicated than the other three media. Meanwhile, this study's results also show that the perspective of the usefulness of the learning media is considered to have good benefits. Zoom is the application/platform that is considered the most useful from other media, while LMS is considered less useful than the other three media.